Oxygen influence in the magnetic and the transport properties of ferroelectric/ferromagnetic heterostructures - Gonzalez Sutter, J. (2017)
Fil: Gonzalez Sutter, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina